Genus Didymocarpus Wall. and a new record of species Didymocarpus purpureobracteatus Smith for the flora of Vietnam from Xuan Lien natural reserve, Thanh Hoa province - Phuong, Vu Xuan; Vu, Dang Quoc; Xuyen, Do Thi (Academia Journal of Biology, 2014)
Species Didymocarpus purpureobracteatus Smith is a new record for the flora of Vietnam. It was regarded as one endemic species to China, but up to now we have found it in Xuan Lien natural reserve (Thanh Hoa province). Voucher specimens were deposited in the Herbarium of the Institute of Ecology and Biological Resources, Hanoi, Vietnam (HN). This species is closed to D. poilanei but differs by bract elliptic or ovate, ca. 3-8 mm long; sepal tube ca. 8-9 mm long, sepal lobed ca. 2-3 mm long. So far,  in Vietnam there were 5 species of the genus Didymocarpus Wall. recorded  D. bonii, D. pulcher, D. kerrii, D. poilanei and D. purpureobracteatus.